2005
DOI: 10.4314/biokem.v16i2.32571
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation excludes protein synthesis inhibition in the tetracycline management of African trypanosomosis

Abstract: Ribonucleotide reductase, an iron requiring enzyme necessary in the production of deoxyribonucleotides required for replication in cell division and proliferation is induced during the S phase of the cell cycle. We have compared the trypanocidal properties of four antibiotics that show bactericidal activities by destabilizing ribosome-mRNA complex to inhibit protein synthesis. Tetracycline and oxytetracycline that have iron chelating properties extended the lifespan of trypanosome infected rats from 6 and 5 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Various reports [11][12][13][14] have indicated that ironchelation could be a potent means of killing African trypanosomes in vitro and in vivo and the prime suspect as target is the enzyme ribonucleotide reductase (RNR). It has been reported that blood stream forms of trypanosomes increase their transferring uptake from hosts by approximately 3 folds in iron depletion 7,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports [11][12][13][14] have indicated that ironchelation could be a potent means of killing African trypanosomes in vitro and in vivo and the prime suspect as target is the enzyme ribonucleotide reductase (RNR). It has been reported that blood stream forms of trypanosomes increase their transferring uptake from hosts by approximately 3 folds in iron depletion 7,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Intracellularly, the iron-dependent, cell cycle related enzyme, ribonucleotide reductase plays a central role in cell division and proliferation 8 . This iron-requiring RNR is presented in T. brucei 9,10 and it has been suggested that it can be exploited for the development of cheap antiparasite therapies including African trypanosomiasis [11][12][13][14] . Drugs of the quinine family have also been suggested to have iron-chelating properties 15,16 .…”
Section: Introductionmentioning
confidence: 99%